Review Artikel: Pengaruh Penggunaan Disintegran Terhadap Waktu Hancur Tabet - Ayu, Adelia (Jurnal Farmasi Sains dan Teknologi, 2025)
Tablets are solid preparations containing medicinal ingredients with or without fillers. Disintegrants are important additional ingredients in tablet formulations that play a role in accelerating the process of tablet disintegration into small particles, thus supporting the release and absorption of active substances in the body. The mechanism of action of disintegrants is opposite to binders and works optimally through water absorption and swelling. Various studies have shown that the type, concentration, and mixing method of disintegrants (intragranular, extragranular, or combination) greatly affect the physical properties of tablets, especially disintegration time. Superdisintegrants such as crospovidone, Primogel, and Amprotab have been shown to significantly accelerate disintegration time. In addition, local natural ingredients such as breadfruit starch, mango seeds, kepok bananas, and ganyong also show potential as alternative disintegrants. The results of the study generally showed that increasing the concentration of disintegrants accelerates the disintegration time of tablets, as long as it does not cause a decrease in physical quality such as hardness and brittleness. Thus, the selection and optimization of disintegrants are crucial aspects in the development of tablets that are effective and meet pharmaceutical quality standards